The Effect of Work-Life Balance and Employee Empowerment on Employee Performance: The Mediating Role of Job Satisfaction - K.C. , Harendra (Journal of Nepalese Management and Research, 2025)
This research investigates the effect of work-life balance and employee empowerment on employee performance within service sector organizations operating in Karnali Province, Nepal. The research utilized a causal-comparative design. Data collection involved distributing validated structured questionnaires to measure work-life balance, employee empowerment, job satisfaction, and employee performance. A convenience sampling method was employed to gather responses from 402 employees working across various service-sector organizations located in Karnali Province. SmartPLS software was used for data analysis. The study’s findings indicate that both work-life balance (WLB) and employee empowerment (EE) have a significant, positive influence on employee performance (EP). Furthermore, job satisfaction (JS) also has a substantial positive effect on EP. The analysis confirmed that JS partially mediates the relationship between WLB and EP, and between EE and EP. This suggests that these organizational practices contribute to better performance not only through a direct mechanism but also indirectly by successfully cultivating higher levels of job satisfaction. The generalizability of these findings might be limited due to the reliance on convenience sampling and the specific focus on only one geographic area. This study contributes to the literature by integrating work-life balance, employee empowerment, and job satisfaction into a unified framework in the context of a developing economy.